Characteristics of PbO-BiO1.5-GaO1.5 glasses melted in SnO2 crucibles - Cerri, José A.; Santos, Iêda M. G.; Longo, Elson [UNESP]; Leite, Edson R.; Lebullenger, Ronan M.; Hernandes, Antonio Carlos; Varela, José Arana [UNESP] (Amer Ceramic Soc, 1998)
PbO-BiO 1.5-GaO 1.5-based glasses are good candidates for optical applications, because of some of their interesting characteristics, such as high refraction indices and high transmission in the ultraviolet (UV), visible (VIS), and infrared (IR) regions. A limited stage in the processing of these glasses is the corrosion that is caused by the melt in all currently used conventional crucibles, such as noble metals (platinum or gold) and Al 2O 3. The absorption of crucible material by the glass composition may reduce the transmission level, the cutoff in the UV-VIS, and IR regions, and the thermal stability. In this study, a SnO 2 crucible has been tested for PbO-BiO 1.5-GaO 1.5 molten glass. Optical and thermal analyses show, in some cases, advantages over the use of platinum and Al 2O 3 crucibles. A visible cutoff value of 474 nm has been measured, and a longer melting time (850°C for 4 h) results in a significant reduction of the O-H absorption band at 3.2 μm.
Keywords: Absorption spectroscopy; Bismuth compounds; Crucibles; Gallium compounds; Lead compounds; Melting; Molten materials; Oxides; Thermoanalysis; Tin compounds; Visible cutoff values; Optical glass